A Comprehensive Review of Bacteriabased Cancer Therapies - Dr. Varunsingh Saggu (Asian Journal of Pharmaceutics (AJP), 2025)
Target-based techniques are part of effective anti-cancer therapy tactics, and they have been shown to be quite effective when compared to more modern therapeutic approaches. Chemotherapy, radiation therapy, immunotherapy, and surgery are all part of traditional anticancer treatment. The ability of malignant cells to “survive even in adverse conditions such as low pH, hypoxia, and high pressure of interstitial fluid that make up the tumor microenvironment” (TME) is one of the main disadvantages of recent cancer treatment methods. We can easily overcome all the shortcomings of the most current treatment and contribute to boosting the effectiveness of target-based therapy by introducing bacteria as powerful innovative agents for anti-cancer therapy. Furthermore, since bacterial anti-cancer treatment is more effective in TME than other options, the sustainability and hyperplastic activity of these malignant cells may be significantly reduced. In addition, bacterial-based cancer treatment (BBCT) may be employed alone or in conjunction with conventional techniques to boost their effectiveness. This essay will discuss the latest developments, present difficulties, and possible future directions of BBCT.